The impact of macroeconomic variables on stock market returns: Evidence from a sample of Arabic countries facing political and economic instability - Alammar, Radwan; Wardeh, Almougheer (International Journal of Business, Economics and Management, 2024)
The main purpose of this study is to determine the presence and timing of the structural breaks in the stock market returns and investigate their impact on the relationship between the macroeconomic variables (namely the inflation rate, the exchange rate, the oil prices) and the stock market returns of a sample of Arab countries facing political and economic instability, namely (Syria, Egypt, Tunisia and Bahrain), during the period (2010-2020). CUSUM test is performed in order to test the presence of structural breaks in stock market indexes. In case there is evidence of structural breaks, Bai and Perron Multiple Breakpoints test is used to identify points in time where significant changes may have occurred. The timing of structural breaks is used as a control variable to examine the impact of the macroeconomic variables on the stock market returns through applying Johansen cointegration test. The results provide evidence of the presence and timing of the structural breaks in the Arab stock markets under study and their role in impacting the relationship between the macroeconomic variables and stock market returns. The study concluded that the dynamics of how the macroeconomic variables affecting the stock market returns depends on the nature and timing of the structural break.